2021
DOI: 10.3390/ijms22168540
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Metabolism in Normal and Malignant Hematopoiesis

Abstract: The hematopoietic system relies on regulation of both metabolism and autophagy to maintain its homeostasis, ensuring the self-renewal and multipotent differentiation potential of hematopoietic stem cells (HSCs). HSCs display a distinct metabolic profile from that of their differentiated progeny, while metabolic rewiring from glycolysis to oxidative phosphorylation (OXPHOS) has been shown to be crucial for effective hematopoietic differentiation. Autophagy-mediated regulation of metabolism modulates the distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 199 publications
(246 reference statements)
0
17
0
Order By: Relevance
“…Mitophagy is important both in normal hematopoietic cell development and in various hematologic malignancies, discussed in detail in a recent review by Stergiou and Kapsogeorgou [88]. In AML, decreased mitophagy was shown to reduce cell proliferation.…”
Section: Mitophagy In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Mitophagy is important both in normal hematopoietic cell development and in various hematologic malignancies, discussed in detail in a recent review by Stergiou and Kapsogeorgou [88]. In AML, decreased mitophagy was shown to reduce cell proliferation.…”
Section: Mitophagy In Cancermentioning
confidence: 99%
“…In addition, mitophagy was found to be prominent in the myeloid lineage in MDS. Interestingly, mitophagy receptor, BNIP3 and NIX, expressions were decreased in MDS, latter in the high-risk group [88][89][90][91][92][93]. Mitophagy inhibitors and inducers are listed in Section 4, Table 3.…”
Section: Mitophagy In Cancermentioning
confidence: 99%
“…Meanwhile, metabolites generated from metabolic pathways also contribute to signaling functions, remodeling the epigenome, and altering the expression of specific sets of genes that can initiate and support cancer development [7]. Accumulating data have demonstrated a role of metabolic reprogramming, including glycolysis, oxidative phosphorylation (OXPHOS), and fatty acid metabolism in AML [8][9][10]. However, substantial studies have shown that the metabolic heterogeneity among AML patients results from multiple factors, including gene mutations and BM microenvironment [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Mitophagy is defined as mitochondria-selective autophagy and plays a role in the elimination of defective mitochondria [31]. Several reports have suggested that depolarization of the mitochondrial membrane potential and ROS production are involved in mitophagy [32][33][34].…”
Section: Mitophagy Occurrencementioning
confidence: 99%